Peningkatan Produktivitas Padi Sawah melalui Pengelolaan Hara Terpadu di Propinsi Riau - Yunizar, Yunizar (Jurnal Agro Teknologi Tropika, 2015)
Increased productivity of paddy rice through integrated nutrient management has been implemented in sub districtRimba Melintang, Regency Rokan Hilir MH 2012. The design used in this study is a randomized block design (RBD ) ,which consists of 9 treatments and 3 replications . The treatment is the application of integrated nutrient of inorganicand organic fertilizers taking into account the needs of the plants and the soil nutrient based fertilizer recommendationsbased on the results of fertilizer recommendations soil testing research results . Treatment includes : 1 ) . Poko ( control) , 2 ) . P1 KCl , 3 ) . P1 , rice straw , 4 ) . P2 , KCl , 5 ) . P2, rice straw , 6 ) . P2 , manure , KCl , 7 ) . P2 , manure , rice straw, 8 ) . P3 , KCl and 9 ) . P3 , straw . Rice varieties planted are Ciherang . Soil analysis is done at the beginning and endof the study . Observations of plant cover ; plant height , number of tillers , number of productive panicles and grain yield. Research results show that the application of integrated nutrient management increase rice production in sub districtRimbaMelintang, Regency Rokan Hilir